Potensi Teknologi Masa Depan terhadap Transformasi Dunia Kerja: Tinjauan Literatur terhadap Kecerdasan Buatan, Otomasi, dan Komputasi Awan - Syalsabilla, Adinda; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the potential impacts of future technologies on the transformation of the workforce using a narrative literature review approach. The primary focus lies on three key technologies: artificial intelligence, automation, and cloud computing. The literature analyzed includes scientific journals and reports from leading global institutions published between 2020 and 2025. This study employs a descriptive and conceptual approach to identify recurring themes and patterns across sources. The findings reveal that technological advancements are driving significant changes in job structures, increasing the demand for advanced digital skills, and introducing new challenges related to inequality and job security. On the other hand, these technologies offer opportunities for human-machine collaboration and flexible work models that may enhance productivity. The study highlights the need for adaptive strategies by workers, organizations, and policymakers in navigating the digital transformation era.